2007
DOI: 10.1158/1078-0432.ccr-07-0760
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Markers of Perifosine Efficacy

Abstract: Purpose: It is critical to develop methods to quantify the early pharmacodynamic effects of targeted therapeutics in vivo to make drug development more efficient and ensure biologically relevant dosing. Furthermore, an ability to identify patients likely to respond to targeted therapeutics would decrease the size, duration, and cost of clinical trials, resulting in more efficient translation to improved patient outcomes. Recent studies suggest that perifosine inhibits the phosphatidylinositol-3 ¶-kinase (PI3K)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 23 publications
2
88
0
Order By: Relevance
“…Blocking simultaneously distinct components of the PI3K/Akt pathway seems to enhance the inhibition of phosphorylation of Akt along with activation of the apoptotic pathway. Recently, it has been shown a statistically significant correlation between the antitumor efficacy of perifosine and quantified downregulation of p-Akt and p-S6 (Hennessy et al, 2007). Moreover, results obtained from a study of perifosine in MT-1 human breast xenograft suggests that immunomodulation may partly contribute to the anticancer activity of this compound (Safa et al, 1998).…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…Blocking simultaneously distinct components of the PI3K/Akt pathway seems to enhance the inhibition of phosphorylation of Akt along with activation of the apoptotic pathway. Recently, it has been shown a statistically significant correlation between the antitumor efficacy of perifosine and quantified downregulation of p-Akt and p-S6 (Hennessy et al, 2007). Moreover, results obtained from a study of perifosine in MT-1 human breast xenograft suggests that immunomodulation may partly contribute to the anticancer activity of this compound (Safa et al, 1998).…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…To accomplish this, we used both reverse-phase protein analyses and immunoblot analyses with phosphospecific antibodies directed at these key downstream signaling molecules (Hennessy et al, 2007). The results revealed that the rare ILK-deficient tumors that arise did not show a significant decrease in signaling through any of these core signaling pathways (Supplementary Figure S3 and S4).…”
Section: Ilk-deficient Tumor Cells Have Regained Their Proliferative mentioning
confidence: 99%
“…Reverse-phase protein lysate microarray Reverse-phase protein microarray was performed as described previously and used to evaluate the expression and the phosphorylation of 40 distinct proteins (Tibes et al, 2006;Hennessy et al, 2007).…”
Section: Immunoblot Analysesmentioning
confidence: 99%
“…is an oral Akt inhibitor that is being tested in phase I/II clinical trials [7][8][9][10][11]; this drug is a synthetic alkylphospholipid (APL) that targets the pleckstrin homology domain of Akt, thereby preventing its translocation to the plasma membrane [12][13][14][15]. Recent reports have shown that the in vitro sensitivity of cancer cell lines to tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) can be considerably increased by cotreatment with perifosine due to significant upregulation of death receptors 4/5 (DR4/5) expression as well as downregulation of the antiapoptotic protein cFLIP [16][17][18].…”
Section: Introductionmentioning
confidence: 99%